Smartphones through children’s eyes: perceived benefits and educational considerations - Gaztañaga, Mirari; Idoiaga-Mondragon, Nahia; Legorburu Fernandez, Idoia; Eiguren Munitis, Amaia (Frontiers in Psychology, 2025)
IntroductionSmartphones have become central to everyday life, especially among children and adolescents. While they provide opportunities for communication, learning, and entertainment, growing concerns persist regarding their association with negative outcomes such as anxiety, depression, and reduced social and cognitive development. Despite the prevalence of these concerns, children’s own perspectives are often overlooked in debates about smartphone regulation and education.MethodsThis mixed-methods study involved a total of 642 children from the Basque Country. Data collection combined quantitative and qualitative approaches to explore children’s perceptions of smartphone use. Participants shared their experiences and opinions through structured questionnaires and open-ended responses, allowing for both statistical analysis and thematic exploration.ResultsChildren identified four main benefits of smartphone use: (1) maintaining social connections and contacting parents in emergencies, (2) accessing information, (3) reducing boredom, and (4) engaging in multimedia entertainment. Ownership status influenced perceived benefits: those with personal devices highlighted communication and academic uses, while those using parents’ devices focused on entertainment. The study also examined the role of smartphone education in schools and family discussions, revealing significant correlations with children’s reported benefits.DiscussionFindings underscore the importance of incorporating children’s voices into digital policy and educational strategies. The study highlights the need for early digital education programs that promote balanced and responsible use. Additionally, it identifies boredom as a potentially constructive driver for creative and emotional development. Adopting a child-centered framework for understanding smartphone use can foster more effective and empathetic approaches to digital wellbeing.